Uridical Reviewon Drug And Cosmetics Imported Chinese Products That Do Not Include Indonesian Language Labels - Yeyen Handoyo; Mohammad Roesli; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The aim of this research is to find out the consumer protection for imported Chinese medicinal and cosmetic products that do not include Indonesian language. This research uses the method. Result The form of consumer protection against the distribution of imported Chinese medicinal and cosmetic products that do not include Indonesian is a form of preventive protection, namely a form of protection with the existence of several regulations such as the UUPK, while repressive protection itself cannot be carried out optimally, this is because consumers themselves do not report when product incompatibilities occur.